Captopril versus enalapril in the protection of the gastric mucosa against NSAID induced gastric mucosal injury in rats - Matloub, Samir Y. N. (Journal of the Faculty of Medicine Baghdad, 2011)
Background: Different mechanisms have been suggested for the development of nonsteroidal antiinflammatory drugs (NSAIDs) induced gastropathy. Angiotensin converting enzyme inhibitors have been suggested to have gastroprotective effects. This study investigates the gastroprotective effects of Angiotensin converting enzyme inhibitors, captopril and enalapril on indomethacin induced gastric mucosal damage in rats . Materials and methods: The study was conducted on 50 adult male albino rats, divided into 5 groups, the first served as a control received the vehicle , the second received indomethacin orally of 60mg/kg. The third and fourth groups were pretreated orally 30 minute prior indomethacin with either captopril or enalapril. In order to study the possible role of nitric oxide (NO) in the gastroprotective effect of captopril; intraperitoneal NG-L-Arginine Methyl Ester (L-NAME) a nitric oxide synthase inhibitor was given 30 minutes prior to captopril administration followed by indomethacin and this served as fifth group. The rats were then sacrificed after 4 hours and their stomachs were isolated and submitted to macroscopical assessment and for the measurement of the gastric prostaglandinE2 (PGE2), and myeloperoxidase (MPO). Results: Captopril in a dose of 15 mg/kg produced a significant reduction (p <0.05) in the gastric damage score .These protective effects were associated with a significant increase (p <0.05) in gastric PGE2 levels and marked decrease (p <0.05) in MPO activity, L-NAME pretreatment didn’t abrogate the effects of captopril. Enalapril pretreatment failed to show the gastroprotective effects of captopril. Conclusions: The prophylactic use of captopril in this study prevented indomethacin induced gastropathy .This protective effect was associated with PGE2 upregulation and decreased oxyradical generation reflected by a decrease in MPO activity .Enalapril failed to produce the gastroprotective effects of captopril.